A K-Band Planar Active Integrated Bi-Directional Switching Heat Applicator With Uniform Heating Profile - Kim, Dongki; Kim, Kihyun; Oh, Jungmin; Cho, Jeiwon; Cheon, Changyul; Kwon, Youngwoo (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2009)
A planar bi-directional microwave heat applicator integrated with active circuits on a single platform is presented in this paper. K-band frequencies have been utilized to facilitate low-power hyperthermia and high-level integration. The active source module implemented with GaAs-based multichip monolithic microwave integrated circuits delivers 1.4 W at 20 GHz into the co-integrated planar applicator, which has three planar coaxial apertures on each side for wide-area bi-directional hyperthermia. The heating volume is further enhanced by employing switched heating, which effectively doubles the hyperthermic volume. The bio-heat equation is solved to find the Optimum Switching time, as well as to achieve uniform heating across the apertures. The effectiveness of the proposed applicator has been demonstrated by in-vitro heating experiments on the pork muscle, which showed 210.6-mm(3) heating volume using only 1.4 W of on-board source power. The entire applicator was realized in a small form factor (5 mm x 50 mm x 0.524 mm) for minimally invasive interstitial insertion. The cost of the hyperthermia system can be drastically reduced by integrating active components on the applicator platform.
Keywords: DIELECTRIC-PROPERTIES; HYPERTHERMIA; TEMPERATURE; ABLATION; ANTENNA; MODEL